miR-204-5p Protects Nephrin from Enzymatic Degradation in Cultured Mouse Podocytes Treated with Nephrotoxic Serum - George Haddad; Judith Blaine (Cells, 2025)
Nephrin is an essential constituent of the slit diaphragm of the kidney filtering unit. Loss of nephrin expression leads to protein leakage into the urine, one of the hallmarks of kidney damage. Autoantibodies against nephrin have been reported in patients with minimal change disease and recurrent focal segmental glomerulosclerosis. Understanding the mechanism of nephrin loss may help improve or lead to the development of novel treatment strategies. In this study, we demonstrated the important function of miR-204-5p expression on the protection of nephrin from anti-nephrin antibodies present in nephrotoxic serum (NTS). In addition, we identified that aspartyl protease cathepsin D is one enzyme that may be involved in nephrin enzymatic degradation and that cathepsin D is a direct target of miR-204-5p gene regulation. The regulation of miR-204-5p expression was determined to be regulated by the long noncoding RNA Josd1-ps. In an NTS in vivo animal model, treatment with the pan aspartic protease inhibitor Pepstatin A ameliorated renal damage. Finally, we showed that the expression of miR-204-5p had a nephrin-protecting function in vitro. Developing a method of delivery of miR-204-5p specifically to podocytes in vivo may provide a novel method of nephroprotection against nephrin autoantibodies.